Effect of Service Quality on Company Customer Satisfaction - Haryati haryati; Haedar Akib; Aris Baharuddin; Andi Cudai Nur; Muh Nasrullah (Universitas Negeri Makassar, 2021)
This study aims to determine the effect of service quality on customer satisfaction of the Makassar City Regional Public Drinking Water Company in Tallo District. This type of research is a descriptive study with a quantitative research design. The data collection technique is done through observation, questionnaire (questionnaire) and documentation. The data analysis technique used consists of descriptive statistical analysis and inferential statistical analysis. In this study, researchers tried to determine how much influence service quality has on customer satisfaction. This study used a survey method, data collection was carried out by observation, questionnaires and documentation and analyzed using SPSS assistance. From the results of data processing for service quality variables obtained a value of 85 percent, So it can be concluded that the service quality of Perumda Drinking Water in Makassar City in Tallo District is in the good category. The results of data processing for the variable customer satisfaction obtained a value of 82 percent, it can be concluded that customer satisfaction of Perumda Air Drinking City of Makassar in Tallo District is in the high / strong level category. From the results of the correlation coefficient analysis, the correlation coefficient is = 0.425, so it can be concluded that the quality of service is correlated with a high level of correlation with customer satisfaction of the Regional Public Drinking Water Company in Makassar City in Tallo District. The results of data processing for the variable customer satisfaction obtained a value of 82 percent, it can be concluded that customer satisfaction of Perumda Air Drinking City of Makassar in Tallo District is in the high / strong level category. From the results of the correlation coefficient analysis, the correlation coefficient is = 0.425, so it can be concluded that the quality of service is correlated with a high level of correlation with customer satisfaction of the Regional Public Drinking Water Company in Makassar City in Tallo District. The results of data processing for the variable customer satisfaction obtained a value of 82 percent, it can be concluded that customer satisfaction of Perumda Air Drinking City of Makassar in Tallo District is in the high / strong level category. From the results of the correlation coefficient analysis, the correlation coefficient is = 0.425, so it can be concluded that the quality of service is correlated with a high level of correlation with customer satisfaction of the Regional Public Drinking Water Company in Makassar City in Tallo District.